PENGARUH BAURAN PEMASARAN DAN STRATEGI PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK TRESURI PADA PT BANK BNI WILAYAH MEDAN - Wiwi Silvia; Aldwin Surya; Rita Margaretha Setianingsih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat-Universitas Darma Agung. (LPPM_UDA), 2022)
The results of the study through the t-test for the marketing mix obtained a tcount is 4.041 > ttable 2,005 and the significance value for the marketing mix variable is 0,000 < alpha 0.05 so it can be concluded that the marketing mix has a positive and significant effect on the decision of purchasing treasury products at Bank BNI Medan Region. The t-test for marketing strategy obtained a value of tcount is 4.158 > ttable 2.005 and the significance value for the marketing mix variable of 0.000 < alpha 0.05 and then it can be concluded that marketing strategies have a positive and significant effect on the purchase decisions of treasury products at Bank BNI Medan Region.The F-test results obtained Fcount 37,331 > Ftable 3,16 and the significance of 0,000 < alpha 0,05 so it can be concluded that the marketing mix and marketing strategy both together have a significant effect on the decision of purchasing treasury products at Bank BNI Medan Region.